2020
DOI: 10.1021/acsaem.0c02406
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Tuning Residual Lithium Compounds and Constructing TiO2 Coating for Surface Modification of a Nickel-Rich Cathode toward High-Energy Lithium-Ion Batteries

Abstract: Nickel-rich layered oxides with excellent specific capacity and reasonable cost have extensively employed as cathode materials for higher energy density lithium-ion batteries (LIBs). However, side reactions caused by the surface contaminations and deterioration of the layered structure especially at high cutoff voltage lead to insufficient cycle life and poor electrochemical performance, which further hinder the commercial development of nickel-rich cathode materials. Herein, an optimized route combining acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The results of residual lithium titration showed that the amounts of residual lithium of S-NCM65 and 5TS-NCM65 were 5695 ppm and 3992 ppm, respectively, indicating that the TiO 2 coating had a signicant effect on the reduction of residual lithium, which may be due to the reaction of TiO 2 with partial residual lithium to form lithium titanate. 31 The decrease in Li 2 CO 3 and LiOH on the surface of the material is conducive to the suppression of the side reaction at the cathode/electrolyte interface. LiOH will react with LiPF 6 in the electrolyte to generate HF, further corroding the electrode material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of residual lithium titration showed that the amounts of residual lithium of S-NCM65 and 5TS-NCM65 were 5695 ppm and 3992 ppm, respectively, indicating that the TiO 2 coating had a signicant effect on the reduction of residual lithium, which may be due to the reaction of TiO 2 with partial residual lithium to form lithium titanate. 31 The decrease in Li 2 CO 3 and LiOH on the surface of the material is conducive to the suppression of the side reaction at the cathode/electrolyte interface. LiOH will react with LiPF 6 in the electrolyte to generate HF, further corroding the electrode material.…”
Section: Resultsmentioning
confidence: 99%
“…At such a high cut-off voltage and high current density, the 94.16% cycling retention rate for 200 cycles (97.16% for 100 cycles) of 5TS-NCM65 is the highest among nickel-rich materials in the literature. 27,30,31,[40][41][42][43][44][45][46] These results indicate that under high cut-off voltage and high current density, coating treatment is an effective method to improve the cycle performance of single crystal materials. Coating with 5000 ppm TiO 2 is the most signicant for improving the cycle performance of single crystal materials.…”
Section: Resultsmentioning
confidence: 99%
“…The signal peaks of Ti 2p 3/2 and Ti 2p 1/2 were observed at 458.3 and 464.3 eV respectively, and both orbital peaks correspond to Ti 4+ in TiO 2 . 39 In the F 1s spectrum (Figure 2e), the signal peak of elemental F was also only detected on the surface of the LCO/ TF-1% sample. The peak at 685 eV is attributed to LiF formed on the LCO surface, which further proves that the gaseous fluorine compound decomposed by TiF 4 reacted with Li exposed on the surface layer during high-temperature heat treatment to generate LiF.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…In the Ti 2p spectrum (Figure d), the signal of Ti was not detected on the surface of the pure LCO sample, but the standard Ti 2p orbital peak spectrum was detected on the surface of the coated LCO/TF-1% sample. The signal peaks of Ti 2p 3/2 and Ti 2p 1/2 were observed at 458.3 and 464.3 eV respectively, and both orbital peaks correspond to Ti 4+ in TiO 2 . In the F 1s spectrum (Figure e), the signal peak of elemental F was also only detected on the surface of the LCO/TF-1% sample.…”
Section: Resultsmentioning
confidence: 99%
“…The popularity of consumer electronics and the rapid development of electric vehicles have put forward higher energy density and longer service life requirements for lithium-ion batteries (LIBs), which are mainly limited by cathode materials. Among the various promising cathode materials, the nickel-rich layered oxides (LiNi x Co y Mn z O 2 , x ≥ 0.6, x + y + z = 1) attract widespread attention due to their extremely high reversible capacity that can even exceed 200 mAh g –1 when the charging voltage exceeds 4.5 V. Except for the contribution of cations, additional capacity is achieved by the redox reaction of anionic oxygen (O 2– /O 2 n – , where 1 < n < 2) during a high charging voltage. , However, Ni-rich materials suffer from severe phase transformation and surface side reactions that cause the capacity and voltage to fade during high-voltage cycling. Therefore, many surface protectors, such as oxides (e.g., Al 2 O 3 , ZrO 2 , TiO 2 ), phosphates (Li 3 PO 4 , FePO 4 , LiFePO 4 ), and fluorides (AlF 3 , LiF, MgF 2 ), were designed to mechanically restrain unwanted structural transformations and inhibit surface side reactions by avoiding direct contact between the cathode materials and the electrolyte.…”
Section: Introductionmentioning
confidence: 99%